Predictive Factors for Pregnancy in IVF: An Analysis of 348 Cycles - Budi Wiweko (Indonesian Journal of Obstetrics and Gynecology, 2010)
Objective: To determine predictive factors for pregnancy after IVF. Method: The subject of this study were three hundred and forty eight IVF cycles in 266 couples who underwent controlled ovarian hyperstimulation in IVF cycles between January 2005 and March 2010. Categorical variables were compared using Chi Square test and continuous variables were analyzed using Independent t-test, p < 0.05 was considered statistically significant. Multivariate logistic regression analysis was done to test correlations between clinical variables and the occurrence of pregnancy. Results: The women’s age significantly influenced pregnancy rate since women under 35 years old has the best chance for pregnancy (56.4%). Endometrial thickness on the day of hCG administration also significantly influenced pregnancy in IVF (p < 0.001) because 64.1% of pregnancy occurred if endometrial thickness ≥ 10.95 mm. Serum FSH on 3rd day of period that can predict ovarian reserve also has significance on pregnancy. On the other hand, 61.5% pregnancy occurred if more than 6 mature oocytes were retrieved (p < 0.001). Among 92 patients of 348 cycles we found strong correlation between AMH level with number of mature oocytes retrieved (p < 0.001; r 0.659). Logistic regression done revealed the couple with best chance of pregnancy can be described as follows: women with endometrial thickness ≥ 10.95 mm, number of mature oocytes > 6 and age under 35 years old. Conclusion: This study enabled the characterization of many prognostic factors for pregnancy. [Indones J Obstet Gynecol 2010; 34-4: 180-4] Keywords: in vitro fertilization, clinical pregnancy, age, mature oocytes, endometrial thickness